Padded Headgear does not Reduce the Incidence of Match Concussions in Professional Men’s Rugby Union: A Case-control Study of 417 Cases - Stokes, Keith A.; Cross, Matthew; Williams, Sean; McKay, Carly; Hagel, Brent E.; West, Stephen W.; Roberts, Simon Paul; Sant’Anna, Ricardo T.; Morrison, Edward; Kemp, Simon (International Journal of Sports Medicine, 2021)
Concussion is the most common match injury in rugby union. Some players wear padded headgear, but whether this protects against concussion is unclear. In professional male rugby union players, we examined: (i) the association between the use of headgear and match concussion injury incidence, and (ii) whether wearing headgear influenced time to return to play following concussion. Using a nested case-control within a cohort study, four seasons (2013–2017) of injury data from 1117 players at the highest level of rugby union in England were included. Cases were physician-diagnosed concussion injuries. Controls were other contact injuries (excluding all head injuries). We determined headgear use by viewing video footage. Sixteen percent of cases and controls wore headgear. Headgear use had no significant effect on concussion injury incidence (adjusted odds ratio=1.05, 95% CI: 0.71–1.56). Median number of days absent for concussion whilst wearing headgear was 8 days, compared with 7 days without headgear. Having sustained a concussion in the current or previous season increased the odds of concussion more than four-fold (odds ratio=4.55, 95% CI: 3.77–5.49). Wearing headgear was not associated with lower odds of concussions or a reduced number of days' absence following a concussion.
Keywords: traumatic brain injury; mTBI; sports injury; injury prevention; equipment; concussion severity